Studying the evolution of the vertebrate circadian clock: the power of fish as comparative models - Foulkes, Nicholas S.; Whitmore, D.; Vallone, D.; Bertolucci, C. (Genetics, genomics and fish phenomics, 2016)
The utility of any model species cannot be judged solely in terms of the tools and approaches it provides for genetic analysis. A fundamental consideration is also how its biology has been shaped by the environment and the ecological niche which it occupies. By comparing different species occupying very different habitats we can learn how molecular and cellular mechanisms change during evolution in order to optimally adapt to their environment. Such knowledge is as important as understanding how these mechanisms work. This is illustrated by the use of fish models for studying the function and evolution of the circadian clock. In this review we outline our current understanding of how fish clocks sense and respond to light and explain how this differs fundamentally from the situation with mammalian clocks. In addition, we present results from comparative studies involving two species of blind cavefish, Astyanax mexicanus and Phreatichthys andruzzii. This work reveals the consequences of evolution in perpetual darkness for the circadian clock and its regulation by light as well as for other mechanisms such as DNA repair, sleep, and metabolism which directly or indirectly are affected by regular exposure to sunlight. Major differences in the cave habitats inhabited by these two cavefish species have a clear impact on shaping the molecular and cellular adaptations to life in complete darkness.
Gesehen am 19.06.2020